Design and topological optimization of rear pressure bulkhead for a typical aircraft. Issue 7 (12th August 2021) - Thakran, Marshal; Meenakshi; Sharma, Jitender; Martin, Charles Gilbert
Abstract : Purpose: The purpose of this paper is to evaluate the model of a rear pressure bulkhead with different design optimizations to meet the pressurized cabin requirements of an aircraft. Design/methodology/approach: This paper presents the results of the static analysis of a dome-shaped rear pressure bulkhead model designed in Catia-v5. Numerical analysis of model meshed in hyper-mesh and solved using Opti-Struct for iterative design optimizations. Findings: All the iterative models are analyzed at 9 Psi. Rear pressure bulkhead designed with L-section stringer shows better results than the model optimized with T-section stringer for the same thickness. The model optimized with L-shaped stinger also reduces the weight of the bulkhead without affecting the structural integrity. Practical implications: It has been concluded in this paper that the selection of specific shapes of the stringers shows a significant influence on weight reduction. Originality/value: This paper provides a topical, technical insight into the design and development of a rear pressure bulkhead. It also outlines the future development of dome-shaped rear pressure bulkhead.